ANALISIS KINERJA KEUANGAN PADA KOPERASI WREDATAMA HARUM KABUPATEN BREBES - Ulul Absor (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2018)
This study took the title of Financial Performance Analysis at the Wredatama Harum Cooperative in Brebes Regency. The formulation of the problem in this study is how the financial performance of the Wredatama Harum Cooperative in Brebes Regency during the period of 2015 to 2017 in terms of liquidity ratios, solvency ratios and profitability ratios. When viewed from the liquidity ratio, in the period of 2015 to 2017 the Wredatama Harum Cooperative can be considered very healthy, this can be seen with the results of the calculation of the current ratio method found that between these years have an average of 62409 percent in each year. Whereas seen from the solvency ratio then: a. Debt to equity ratio (total debt to equity ratio) The total debt to equity ratio from 2015 to 2017 the ratio of debt to equity in the Wredatama Harum Cooperative has an average of 19.30 percent, which is below 70 percent. This means that in terms of the ratio of debt to equity, the cooperative's ability to meet its obligations is very efficient. b. Debt to asset ratio (total debt to asset ratio) The calculation of the debt to assets ratio from 2015 to 2017 solvency ratio when viewed from debt to total assets at the Wredatama Harum Cooperative has an average of 15.54 percent which means below 40 percent which means that the cooperative's ability to its obligations is very efficient . While the profitability ratio : a. Gross profit margin The calculation of gross profit margin from 2015 to 2017 in the Wredatama Harum Cooperative in Brebes Regency has an average of 16.24 percent which means that in the period 2015 to 2017 in terms of the ratio of gross profit margin the cooperative's ability to generate profits is well. b. Net profit margin The calculation of the net profit margin in the Wredatama Harum Cooperative in Brebes Regency has an average of 15.52 percent, which means that in the period 2015 to 2017 in terms of the ratio of the net profit margin the cooperative's ability to generate profits is good. c. Earning power of total investment The calculation of earnings power of total investment in the Wredatama Harum Cooperative in Brebes Regency has an average of 2.80 percent which means that in the period 2015 to 2017 in terms of the ratio of earnings power of total investment the cooperative's ability to generate profits is not good.